Pengaruh Variasi Prekursor Terhadap Morfologi dan Aktivitas Antibakteri Nanopartikel Tembaga Menggunakan Reduktor Ekstrak Daun Gambir - Elisma, Netri; Emriadi , Emriadi; Darmawi, Ahmad (REACTOR: Journal of Research on Chemistry and Engineering, 2023)
Research on synthesis copper nanoparticles has been carried out by the reduction method with a green synthesis approach using extracts of gambir leaves (Uncaria gambir Roxb). Gambir leaf extract contains polyphenol compounds uses as a natural reducing agent to reduce copper cation from variations of prekursor (CuSO45.H2O, Cu(NO3)2.3H2O and CuCl2.2H2O). The formation of copper nanoparticles (CuNP) colloid is visually shown by color change from light brown to dark brown. Absorption peak in UV-Vis spectrophotometer analysis at 405 -427 nm which is a specific wavelength of copper nanoparticles base on phenomenon of Surface Plasmon Resonance (SPR). The X-Ray Diffraction (XRD) analysis showed formation of CuNP with a face centered cubic (fcc) crystal structure. The result of Transmission Electron Microscope show the synthesized CuNP was spherical with particle size diameter 15nm for CuSO4 prekursor, 25 nm for Cu(NO3) prekursor and 28 nm for CuCl2 prekursor. The size of nanoparticles influenced of type prekursor anions. The antibacterial activity of the synthesized nanoparticles was also tested using pathogenic bacteria Escherichia coli and Staphylococcus aureus. The results showed that copper nanoparticles were promising antibacterial agents. Antibacterial activity test on copper nanoparticles were found to have higher antibacterial activity against Gram positive bacteria S. aureus than Gram negatif E. coli.